1981
DOI: 10.3109/00099308109035070
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Some Psychological Parameters in a Population of a Hg Extraction Plant

Abstract: 52 workers of a plant transforming Hg mineral were subjected to psychological investigation in order to detect behavioral alterations which might be related to Hg exposure. A group of 29 subjects living in the same area was used as the control. The test battery included reaction times, mental efficiency measures, and personality indexes for a total of 33 variables. Results were analyzed through statistical elaboration using parametric tests. Efficiency and memory measures could discriminate exposed individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
3
14
1
Order By: Relevance
“…These three functions were selected for the following assessments. To obtain a conclusive set of data, those studies which did not provide test results for each of these domains (Camerino et al 1981;Williamson et al 1982;Roels et al 1985;Gonzalez-Ramirez et al 1995;Ritchie et al 1995;Lucchini et al 2002) had to be excluded. The reduction resulted in a total of 11 studies providing averaged effect sizes for each of the three functions (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…These three functions were selected for the following assessments. To obtain a conclusive set of data, those studies which did not provide test results for each of these domains (Camerino et al 1981;Williamson et al 1982;Roels et al 1985;Gonzalez-Ramirez et al 1995;Ritchie et al 1995;Lucchini et al 2002) had to be excluded. The reduction resulted in a total of 11 studies providing averaged effect sizes for each of the three functions (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported neurobehavioral effects related to motor and cognitive functions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in humans during ongoing exposure to mercury vapors. Contrary to the large number of studies on currently exposed workers, few epidemiologic studies have focused on the long-term effects on workers who are no longer exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobehavioral effects of occupational exposure have been described as falling into the 3 major groups of alterations in emotional state, effects on cognitive functions, and effects on motor functions (1,2). Ongoing exposure to lower concentrations of mercury vapors has been associated with increased hand or finger tremor, subclinical changes in coordination, neuromuscular functions, and deficits in memory and attention (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Magos (21) suggested that it may be a mistake to relate defects to exposure estimates valid at a time when the possibility of higher exposure in the past cannot be excluded.…”
mentioning
confidence: 99%
“…Studies on current exposure of workers to mercury [57][58][59][60][61][62][63][64][65][66][67][68][69] were mostly conducted on workers in industry (chlorine-alkaline factories, thermometer factories, mercury extraction plants), and in one case on gold miners in the Philippines who use large amounts of mercury without any protection [59]. Correlations between the amount of Hg excreted in urine and measures of cognitive abilities (memory tests, attention span) were always significant and negative, i.e., the more mercury excreted the worse the test results.…”
Section: Mercury Exposure In Workersmentioning
confidence: 99%